IMPLEMENTASI TEORI BELAJAR KONSTRUKTIVISME DALAM PEMBELAJARAN MAHARAH KALAM MENGGUNAKAN COOPERATIVE LEARNING DI MADRASAH TSANAWIAH - Shidiq, Fauzie Muhammad; Dewi, Aprilianing Tyas Tri Tungga; Budianto, Langgeng; Hasanah, Mamluatul (Universitas Islam Negeri Mataram, 2024)
Constructivism theory is a learning theory that is oriented towards forming the structure of thought patterns and students' understanding of the material through experience and the learning process. This form of implementation in the field, especially in learning maharah kalam in Arabic, can be supported using the cooperative learning method. This research aims to determine the implementation of constructivist learning theory in maharah kalam learning using the cooperative learning method. This type of research is field research with a descriptive qualitative approach carried out at Madrasah Tsanawiah Satu Atap Al-Hidayah, Batu City, East Java. Data collection techniques use observation techniques and interview techniques. The data analysis used is the Miles, Huberman and Saldana analysis technique with three steps, namely condensing data, presenting data, and drawing conclusions or verification. The results of this research include the following (1) implementation of constructivist learning theory in maharah kalam learning at Madrasah Tsanawiah Satu Atap Al-Hidayah, Batu City with the cooperative learning method applied according to the steps and principles of learning, so as to provide a pleasant learning experience for students . (2) the problems encountered in implementing constructivist learning theory are a lack of initiative in discussing learning material and a lack of motivation in learning Arabic, so that efforts to deal with the problem of implementing constructivist learning theory are for teachers to provide encouragement and motivation in learning Arabic and make improvements- improvements in learning.